Frugal innovation in the Turkish leather industry: Roles of knowledge management, transformational leadership, and sustainable investment - Edlbi, Seyma Sahin; Yilmaz, Mustafa K (International Journal of Management and Sustainability, 2026)
This study examines the impact of knowledge management, transformational leadership, and investments on frugal innovation in 40 Turkish small and medium-sized leather companies for the year 2024. Quantitative data were collected using a semi-structured questionnaire and analyzed with PLS-SEM. Additionally, interviews with senior managers were categorized and coded for qualitative analysis of frugal innovation and knowledge management practices. The results indicate that transformational leadership, knowledge management, and investments significantly contribute to frugal innovation. Moreover, knowledge management is the strongest predictor of frugal innovation (β=0.421, p<0.001), followed by investments (β=0.313, p=0.042), whereas transformational leadership is the strongest predictor of knowledge management (β=0.521, p<0.001). These findings demonstrate that organizations' intangible capabilities, such as knowledge, skills, and organizational culture, facilitate frugal innovation when operating under resource constraints. The evidence further suggests that effective knowledge management practices can serve as an alternative to additional investments in tangible assets, such as machinery or technology. The results offer valuable insights for managers to align investments with a knowledge-driven strategy and to adopt transformational leadership that promotes knowledge sharing for frugal innovation. From a practical perspective, this research provides managers and policymakers with useful, evidence-based recommendations to enhance competitiveness and sustainability in traditional manufacturing sectors through frugal and knowledge-based innovation approaches.